The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/ijc.24075
|View full text |Cite
|
Sign up to set email alerts
|

Different outcome of invasive cervical cancer associated with high‐risk versus intermediate‐risk HPV genotype

Abstract: Human papillomavirus (HPV) DNA sequences are associated with the large majority of invasive cervical carcinoma but the role of specific genotype(s) in the outcome of the disease is still debated. To determine the viral epidemiology in the French population of patients and the prognostic value of HPV genotypes in cervical cancer, we performed a retrospective study in 515 patients treated in our Institution from 1985 to 2005. Ninety-six percent of the cases were found associated with HPV DNA whereas 4% remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 39 publications
3
36
1
3
Order By: Relevance
“…The higher prevalence of HPV16/18/45 in tumors developed in younger patients compared with intermediate-risk HPV genotypes could be explained by different oncogenicity of HPV genotypes. Similar results were observed by De Cremoux et al 14 It was reported that ICCs related to HPV types 16, 18, and 45, irrespective of histological type, are diagnosed an average of 4 years earlier than are those caused by other high-risk HPV types. 18 That is in agreement with the observation that HPV types 16, 18, and 45 are more likely to be integrated into the human genome than are the other HPV types and that precancerous lesions induced by these HPV genotypes progress to ICC in a substantially shorter time compared with lesions induced by HPV types 31 and 33.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher prevalence of HPV16/18/45 in tumors developed in younger patients compared with intermediate-risk HPV genotypes could be explained by different oncogenicity of HPV genotypes. Similar results were observed by De Cremoux et al 14 It was reported that ICCs related to HPV types 16, 18, and 45, irrespective of histological type, are diagnosed an average of 4 years earlier than are those caused by other high-risk HPV types. 18 That is in agreement with the observation that HPV types 16, 18, and 45 are more likely to be integrated into the human genome than are the other HPV types and that precancerous lesions induced by these HPV genotypes progress to ICC in a substantially shorter time compared with lesions induced by HPV types 31 and 33.…”
Section: Discussionsupporting
confidence: 89%
“…Total DNA was extracted by a commercially available kit (QIA amp DNA mini kit, Qiagen, Valencia, CA) following the manufacturer's recommendations and stored at j20-C until use. All samples were then screened for the presence of HPV 14 Polymerase chain reaction amplification using generic primers was done in a 50-HL volume, and included 1Â enzyme buffer, 2-mmol/L MgCl 2 , 0.2 mmol/L of deoxyribonucleotide triphosphate dNTP, 1.25 U Taq Gold DNA polymerase (Applied Biosystems, Foster City, CA) and 1 Hmol/L of each HPV type 3 ¶ and 5 ¶ primers. The amplification ramp included 1 minute at 94-C, then 2 minutes at 40-C and 1 minute 30 seconds at 72-C for 40 cycles.…”
Section: Sample Preparation and Hpv Genotypingmentioning
confidence: 99%
“…The global rate of HPV-negative invasive carcinoma is 10.1%, ranging from 2% to 26.1%. 10 Although several reasons may be evoked to account for the potential false negativity of viral analysis (rare or not yet cloned HPV, loss of viral DNA sequences during the tumor process, DNA degradation in some of the samples, lack of methodology, etc), it has also been hypothesized that a small proportion of ICC, particularly in the population of older women, may be driven by HPVindependent oncogenic mechanisms, 10 the prognosis of which has been shown to be poor. 11 There were many similarities in HPV type-specific distribution across the regions studied.…”
Section: Discussionmentioning
confidence: 99%
“…Positive control-plasmids and two independent negative controls were amplified in each run. All samples were tested for DNA integrity by PCR using primers for the human GAPDH gene (9). The presence of HPV 6/11 was demonstrated by five independent PCR analysis, on formalin-fixed paraffin-embedded tumor tissue from the bone metastatic lesion.…”
Section: Case Reportmentioning
confidence: 99%